factorize 4(ab+1)^2-9(a-1)^2
Answers
Answered by
0
check the solution abd answer
hope its help you
hope its help you
Attachments:
![](https://hi-static.z-dn.net/files/d3e/103367fd860c8eee183d12f3d80d3d85.jpg)
Answered by
0
4(ab + 1)² - 9(a - 1)²
= {2(ab + 1) }² - {3(a - 1)}²
= (2ab + 2 )² - (3a - 3)²
use formula, x² - y² = (x - y)(x + y)
= (2ab +2 + 3a - 3)(2ab +2 -3a + 3)
= (2ab +3a - 1)(2ab -3a +5)
= {2(ab + 1) }² - {3(a - 1)}²
= (2ab + 2 )² - (3a - 3)²
use formula, x² - y² = (x - y)(x + y)
= (2ab +2 + 3a - 3)(2ab +2 -3a + 3)
= (2ab +3a - 1)(2ab -3a +5)
Similar questions